2017
DOI: 10.1093/gbe/evx020
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Functional Diversification of the Deubiquitinating Enzyme Superfamily

Abstract: Ubiquitin and ubiquitin-like molecules are attached to and removed from cellular proteins in a dynamic and highly regulated manner. Deubiquitinating enzymes are critical to this process, and the genetic catalogue of deubiquitinating enzymes expanded greatly over the course of evolution. Extensive functional redundancy has been noted among the 93 members of the human deubiquitinating enzyme (DUB) superfamily. This is especially true of genes that were generated by duplication (termed paralogs) as they often ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 96 publications
1
24
0
Order By: Relevance
“…1E and G, Table S3). We and others found that USP15 (Baker et al, 1999) is expressed in the early progenitor compartment (LSK) and in HSC (Cabezas-Wallscheid et al, 2014;Lancini et al, 2016), as well as in blood and in splenic B cells (Lancini et al, 2016;Vlasschaert et al, 2017). Together with our screen results, these data suggest a potential role for USP15 in hematopoiesis, though no functional study in vivo has yet been reported.…”
Section: In Vivo Rnai Screens For Deubiquitinating Enzymes (Dubs) Idesupporting
confidence: 79%
“…1E and G, Table S3). We and others found that USP15 (Baker et al, 1999) is expressed in the early progenitor compartment (LSK) and in HSC (Cabezas-Wallscheid et al, 2014;Lancini et al, 2016), as well as in blood and in splenic B cells (Lancini et al, 2016;Vlasschaert et al, 2017). Together with our screen results, these data suggest a potential role for USP15 in hematopoiesis, though no functional study in vivo has yet been reported.…”
Section: In Vivo Rnai Screens For Deubiquitinating Enzymes (Dubs) Idesupporting
confidence: 79%
“…The ancestral vertebrate genome appears to have encoded 61 DUBS, and the expanded repertoire of modern vertebrates is largely the product of two rounds of whole genome duplication (referred to as 2R‐WGD) dating to the Cambrian period roughly 500 million years ago; a smaller number arose from small segmental duplications or retrotransposition events. Most duplicated genes are silenced as the result of negative selection or genetic drift, and their pseudogenization or ultimate loss is consistent with the absence of the even greater abundance of DUBs predicted to have been generated by 2R‐WGD . The remaining duplicates can have a high degree of sequence similarity, particularly those arising from WGD (designated ohnologues in recognition of Susumu Ohno who explained the prevalence and origin of such duplicates).…”
Section: What Are the Origins Of The Deubiquitinating Enzyme Superfammentioning
confidence: 61%
“…The activities of enzymes promoting or opposing the assembly of chains are in many cases regulated by post‐translational modifications of the enzymes (notably by phosphorylation events), allowing the dynamic fine‐tuning of ubiquitin‐mediated processes in response to changes in cellular milieu. The genomes of metazoan organisms encode in the order of 100 DUBs and we have recently provided an evolutionary account of their origins . For the analysis that follows, we chose to concentrate on the state of affairs in vertebrate DUBs—in particular on the ubiquitin‐specific proteases (which comprise the largest family of DUBs in vertebrates).…”
Section: What Are the Origins Of The Deubiquitinating Enzyme Superfammentioning
confidence: 99%
See 2 more Smart Citations